Multiply (x – 2)(3x + 4) using the distributive property. Select the answer choice showing the correct distribution.
A. (x)(3x + 4) + (x – 2)
B. (x)(3x) + 4(x) + 3x + 4
C. (x – 2)(3x) + (x – 2)(4)
D. (x – 2)(3x) + (3x)(4)n.

Respuesta :

Answer: Choice C)

(x-2)(3x) + (x-2)(4)

======================================

How to get this answer? One easy way that might work is to let y = x-2, which will allow us to do a replacement.

We will go from (x-2)(3x+4) to y(3x+4). Now use the distributive property to multiply the y term by each term inside

y(3x+4) = y*3x + y*4 = (y)*(3x) + (y)*(4)

The last step is to re-introduce y = x-2 back in. So replace y with x-2 like so

(y)*(3x) + (y)*(4) = (x-2)*(3x) + (x-2)(4)